Hilbert filter based FPGA architecture for power quality monitoring. (December 2019) - Santos-Hernandez, Jesus A.; Valtierra-Rodriguez, Martin; Amezquita-Sanchez, Juan P.; Romero-Troncoso, Rene De J.; Camarena-Martinez, David
Highlights: FPGA implementations are suitable for online real-time power quality monitoring. Hilbert Filter can be used to obtain the envelope of the voltage signal. Power Quality Disturbances affect most of electrical equipment. Power quality monitoring is necessary to early detection of disturbances. Abstract: Power quality (PQ) related studies have become more relevant in recent years since the advent of modern industry related processes and technologies. As a result, PQ strategies have been formulated, facilitating a more efficient control in the generation and distribution of energy resources, therefore reducing both the operational cost for the provider, as well as the service fee for the consumer. This project develops a Hilbert Filter based methodology to monitor power quality indicators, through the analysis of voltage signals in order to detect disturbances that cause instability, quality drops or interruptions. The proposed methodology is implemented online, using digital signal processing based on field programmable gate arrays (FPGAs). As a result, a novel and simple methodology that detects the most common and important voltage disturbances for monitoring PQ is presented, as well as a discussion on its performance when compared to other current software-based alternatives available on the field.